Detection of generated free radicals, lipid peroxidation and some trace elements status in Egyptian patients with chronic hepatitis C. (Journal of Nuclear Technology in Applied Science, 2019)
Hepatitis C virus (HCV) is the etiological agent accounting for chronic liver disease in approximately 2–3% of the population worldwide. In Egypt, HCV infection has become one of the national health problems. The aim of the suggested study was to investigate if any correlation exists between total free radicals generated in chronic hepatitis C patients and some trace elements in blood and urine. The study included 104 subjects, 22 healthy controls and 82 CHC patients grouped as follows: Gr I (control group), Gr II [compensated chronic liver disease (without cirrhosis)], Gr III [decompensated liver cirrhosis (with cirrhosis)] and Gr IV [(hepatocellular failure (end stage liver disease)].Correlations of total free radicals and malondialdehyde )MDA( with other trace elements were studied in different groups. Blood and urinary trace elements concentrations varied among the different stages of HCV patients studied groups. The correlation coefficient between the different variables independently changed. Results of the present study revealed that total free radicals, MDA, blood copper (Cu), urinary zinc (Zn) as well as the total calcium (Ca) and ionized calcium (iCa) concentrations were significantly increased in all CHC patients groups, while blood Zinc (Zn) and selenium (Se) concentrations were significantly decreased in all CHC patients groups compared to those of control group.The urinary cupper (Cu) concentration was significantly elevated only in Gr II. Gr III and Gr IV showed significant low values of blood iron (Fe). Conclusion: blood and urinary trace elements profile was suggested to be a good indicator for assessing liver damage in chronic HCV patients. Oxidative stress with subsequent increase or decrease in blood and urinary trace elements in hepatitis C infected individuals could happen at various stages of liver damage causing impairment in the levels of measured trace elements. The correlation between trace elements and either total free radicals or MDA showed different pattern according to the stage of the disease.
Keywords: Chronic hepatitis C; oxidative stress; Trace elements; Ca; iCa